Study on Omission Plot Technique in Popcorn - Kaduwal, Sangita; Pokharel, Bhanu Bhakta; Karki, Tika Bahadhur; Neupane, Reshama; Bhattarai, Rajendra Kumar; Chaulagain, Bhimsen; Ghimire, Prakash; Gyawaly, Pankaj; Das, Soni Kumari (Agronomy Journal of Nepal, 2024)
There are various limiting factors in production of popcorn in Nepal among one of them is lack of limited information on nutrient management particularly the macronutrient nitrogen, phosphorous and potassium. Therefore, a field experiment was conducted at National Agronomy Research Centre, Khumaltar, Nepal to study the limiting nutrient for popcorn Lumle yellow in 2022/23 and 2023/24 in loam soil. The experiment consisted of five treatments and four replications arranged in randomized complete block design. Five different treatment comprised of FYM (unfertilized/farmer practice), –N,+PK (N omitted), -P,+NK (P omitted) ,-K+NP (K omitted), +NPK applied plots. In 2022/23 and 2023/24 +NPK applied treatment produced significantly highest grain yield of 4.27 t ha-1 and 3.13 t ha-1 while N omitted treatment gave lowest grain yield of 1.36 t ha-1 and 1.30 t ha-1 respectively and this yield was at par with only FYM applied treatment. Grain yield levels obtained for different fertilizer treatments were ranked as +NPK>-P,+NK>-K,+NP>FYM>-N. The results concluded that application of optimum doses of three primary nutrients such as nitrogen, phosphorus and potassium were essential to achieve optimum growth and productivity of maize.